LncRNA XLOC_006390 promotes pancreatic carcinogenesis and glutamate metabolism by stabilizing c-Myc. (28th January 2020) - He, Jun; Li, Fazhao; Zhou, Yan; Hou, Xuyang; Liu, Sushun; Li, Xinchun; Zhang, Yawei; Jing, Xiaoqian; Yang, Leping
Abstract: The role of lncRNAs in the regulation of glutamate metabolism and metabolic reprogramming of pancreatic cancer (PC) during nutrient deprivation is largely unknown. Our study found that alpha-ketoglutarate (aKG) levels were significantly reduced in the absence of XLOC_006390. We subsequently confirmed that the decrease in aKG was mainly due to the downregulation of glutamate dehydrogenase 1 ( GDH1 ) at the mRNA level. Therefore, we first screened transcription factors targeting the GDH1 gene promoter and confirmed that c-Myc regulates GDH1 transcription. c-Myc binds to the promoter of GDH1 and activates its transcription. Downregulation of GDH1 mRNA levels by XLOC_006390 deletion could be rescued by overexpression of c-Myc. Overexpression of XLOC_006390 promoted the protein stability of c-Myc by blocking its ubiquitination. Clinically, XLOC_006390 was positively correlated with the mRNA level of GDH1, and c-Myc positively regulated GDH1 gene expression, which was tightly associated with PC patient prognosis. The dysregulated lncRNA/c-Myc axis increased glutamate metabolism, promoting PC progression to a higher stage. Therefore, XLOC_006390/c-Myc may be a potential target for PC, and its abnormal activation also indicates the progression of PC. Highlights: High expression of LncRNA XLOC_006390 promotes pancreatic carcinogenesis. Expression of LncRNA XLOC_006390 is positively correlated with GDH1 mRNA level in pancreatic cancer patients. LncRNA XLOC_006390 protects c-Myc from ubiquitylation and subsequent degradation. The LncRNA XLOC_006390/c-Myc/GDH1 axis is a therapeutic target for pancreatic cancer.